Differences in Effectiveness of Antibacterial Power Between Cocoa Peel Extract (Theobroma cocoa L.) and Benzalkonium Chloride 0.1% Against Staphylococcus aureus (In Vitro) - Tamara Yuanita; Mohammed Alaqsha Brysoul Ceson; Agus Subiyanto (Universitas Airlangga, 2021)
Background: Staphylococcus aureus is a gram-positive bacteria play a role in the formation of dental biofilm which iscausing dental caries. During tooth preparation, to stop the growth of bacteria, a cavity cleaning agent is given using achemical, namely Benzalkonium Chloride (BAC) 0.1%, but BAC has disadvantages including allergic reactions, tolerantmicrobes, and resistance. Therefore, it is hoped that there will be herbal ingredients that can be used as an alternative.Cocoa peel extract has active compounds of tannins, flavonoids, alkaloids, terpenoids, and saponins which haveantibacterial concentration 6% according to safe concentrations. Purpose: To explain the difference in the effectivenessof the antibacterial power of 6% cocoa peel extract and 0.1% BAC against Staphylococcus aureus (in vitro). Methods:This study was a laboratory experimental in vitro with the posttest only control group design. Using the diffusion methodfor Staphylococcus aureus that divided into two parts, 6% cocoa peel extract and 0.1% BAC. Each petri dish was givendisc paper dripped with 0.01 ml of each test material, then incubated for two days and observed the diameter of theinhibition zone. Results: The average diameter of the inhibition zone formed in the 6% cacao peel extract was 11.5288mm and BAC 0.1% was 18.2925 mm against Staphylococcus aureus. Conclusion: There was a significant difference inthe effectiveness of antibacterial power (p <0.05) between 6% cacao peel extract (Theobroma cacao L.) and 0.1% BACagainst Staphylococcus aureus (In Vitro).